School Dental Services Theoretical Model-Based on Geographic Information System in Al-Madinah, Saudi Arabia - Amal Aqeeli; Alla T. Alsharif; Marc Tennant; Estie Kruger (MDPI AG, 2023)
The study aimed to design a geographic theoretical model for school dental services (SDS) in Al-Madinah, Saudi Arabia (SA), using a geographic information system (GIS). The location of all primary public schools and the student population at each school were obtained from the General Administration of Education in Al-Madinah Al-Munawwarah Region website. The geographic modeling for SDS was analyzed using GIS according to two models. A scenario was developed to simulate the demand for dental care for the two models based on schoolchildren's estimated oral health profile. The areas with the higher number of schools; higher number of students; and dense child population as presented in the map suggest the future location of SDS. The total number of dentists required to work in SDS settings was 415 for the first model, and 277 for the second model. The suggested average number of dentists per district in the highest child population density districts is 18 dentists in the first model, compared to 14 in the second model. Establishing SDS is suggested as a solution to the persistently high prevalence of dental caries among schoolchildren in Al-Madinah and SA in general. A model was suggested for SDS with a guide of the proposed SDS locations and the number of dentists to hire for the services to meet the child population's oral health needs.